2005
DOI: 10.1177/0361198105191200105
|View full text |Cite
|
Sign up to set email alerts
|

Speed Factors on Two-Lane Rural Highways in Free-Flow Conditions

Abstract: The mean free-flow speed and its variability across drivers are considered important safety factors. Despite a large body of research on operating speeds, there is still much to learn about the factors of free-flow speeds, especially on tangent segments of two-lane rural highways. The roadway factors of speed dispersion across drivers are largely unknown. Also, the use of the entire free-flow speed distribution suggested by other authors has not yet been addressed. Consequently, the existing models are not aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 13 publications
3
23
0
Order By: Relevance
“…Vehicles are safe, when the preferred speed in a horizontal curve is equal to or less than its safe speed. Now, curves with radius 500 m or less are considered as sharp (Figueroa Medina, Tarko 2005). Sharp horizontal curves affect the preferred speed (Fitzpatrick et al 2000a;Jacob, Anjaneyulu 2013;Russo et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vehicles are safe, when the preferred speed in a horizontal curve is equal to or less than its safe speed. Now, curves with radius 500 m or less are considered as sharp (Figueroa Medina, Tarko 2005). Sharp horizontal curves affect the preferred speed (Fitzpatrick et al 2000a;Jacob, Anjaneyulu 2013;Russo et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have found that V 85 increases with increase in curve radius; however, remains unchanged for flatter curve (Abdul-Mawjoud, Sofia 2008;Fitzpatrick et al 2000b;Collins et al 1999). Flatter curves have radius of 1700 ft (i.e., 518 m) or more (Figueroa Medina, Tarko 2005). Russo et al (2016) reported that curves having radius more than 500 m do not influence driving performance in horizontal alignment.…”
Section: Introductionmentioning
confidence: 99%
“…Medina and Tarko [32] employed an ordinary least squares method to estimate a customized regression equation for any intended percentile. The resulting models represent a linear combinations of factors associated with the mean and the standard deviation of the speed distribution.…”
Section: Model Descriptionmentioning
confidence: 99%
“…Inclusion of operating speed in the design phase and the evaluation of the road alignment consistency is in the focus of many significant researches in recent years (Gibreel et al 1999(Gibreel et al , 2001Ottesen, Krammes 2000;Hassan 2004;Fitzpatrick et al 2005;Marchionna, Perco 2008;Perco 2008;Medina, Tarko 2005;Cafiso, Cerni 2012;Wang et al 2013).…”
Section: Data Collectionmentioning
confidence: 99%